2006
DOI: 10.1021/jp056097z
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Oligomerization of Aqueous Pyruvic Acid

Abstract: The 320 nm-band photodecarboxylation of aqueous pyruvic acid (PA), a representative of the alpha-oxocarboxylic acids widely found in the atmospheric aerosol, yields 2,3-dimethyltartaric (A) and 2-(3-oxobutan-2-yloxy)-2-hydroxypropanoic (B) acids, rather than 3-hydroxy-2-oxobutanone as previously reported. A and B are identified by liquid chromatography with UV and ESI-MS detection, complemented by collisionally induced dissociation and 2H and 13C isotope labeling experiments. The multifunctional ether B gives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

29
315
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(347 citation statements)
references
References 78 publications
29
315
2
1
Order By: Relevance
“…Organic polymers have been identified as important contributors to SOAs. These polymeric species do not result from gas phase reactions (11) but rather appear to be products of organic reactions in condensed (aqueous) phase, where high-molecular-weight compounds, polymers, and oligomers can be generated (1,5,(12)(13)(14)(15). Recent results have mainly addressed radical reactions in aqueous environments (5,7,16), with only a few using direct photolysis (13,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Organic polymers have been identified as important contributors to SOAs. These polymeric species do not result from gas phase reactions (11) but rather appear to be products of organic reactions in condensed (aqueous) phase, where high-molecular-weight compounds, polymers, and oligomers can be generated (1,5,(12)(13)(14)(15). Recent results have mainly addressed radical reactions in aqueous environments (5,7,16), with only a few using direct photolysis (13,17).…”
mentioning
confidence: 99%
“…These polymeric species do not result from gas phase reactions (11) but rather appear to be products of organic reactions in condensed (aqueous) phase, where high-molecular-weight compounds, polymers, and oligomers can be generated (1,5,(12)(13)(14)(15). Recent results have mainly addressed radical reactions in aqueous environments (5,7,16), with only a few using direct photolysis (13,17). The need for understanding organic reaction mechanisms in aqueous solutions representative of aqueous media in the atmosphere (aerosols, cloud droplets, fog, and rain) has been recognized (1,2,7,18).…”
mentioning
confidence: 99%
“…When examined in its entirety, the evidence for the production of acetoin, lactic, and acetic acids in PA photolysis is irrefutable, and the mechanism presented is sound, being grounded in theoretical calculations as well as supported by the older literature (5,6), and providing an alternative explanation of Guzman et al's prior published results (3,4).…”
mentioning
confidence: 82%
“…Very recently, some laboratory studies have shown that oligomers are produced in the liquid phase after aqueous phase hydration and/or photooxidation of some of the oxidation products of isoprene, i.e. glyoxal (Hasting et al 2005;Loeffler et al 2006;Carlton et al 2007), methylglyoxal (Loeffler et al 2006;Altieri et al 2008), pyruvic acid (Guzmán et al 2006;Altieri et al 2006;Carlton et al 2006), methacrolein El Haddad et al 2009), and glycolaldehyde (Perri et al 2009). The chemical pathways leading to the observed oligomers have been investigated by very few authors.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%
“…Alternatively, there is evidence that radical processes may also contribute to the formation of oligomers in the aqueous phase. Kinetic studies of the formation of oligomers lead some authors to propose combination reactions of organic radicals during the aqueous phase direct photolysis of pyruvic acid (Guzmán et al 2006) (Figure 16) or during OH-initiated oxidation of methacrolein and methylvynilketone Liu et al 2010). For all aqueous phase studies, the formed oligomers have shown molecular masses up to 1400 Da (see the mass spectrum in Figure 15), and are thus non volatile material, which is likely a source of SOA after cloud's processing.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%